Cervical leiomyoma: a rare case with unusual presentation - Wakode, Shamrao Ramji; Lodha, Roshni Vinod (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Leiomyomas or fibroids are the most common benign pelvic tumors in females that grow mono-clonally from the smooth muscle cells of the uterus. Most common tumors of the uterus are fibroids but cervical fibroid is rare during pregnancy with different management difficulties but cervical leiomyomas are less than 5% of all leiomyomas. A middle-aged female patient came to the obstetric opd with complaints of amenorrea for 2 months, per vaginal spotting and abdominal pain for 5 days. Her obstetric score is gravida 2 para 1 living 1. She has no h/o of urinary retention, urgency, constipation or mass per vagina. There is no history of bleeding during coitus. This case is of great importance not only because of its atypical presentation, but because we are dealing with rare pathology that can have consequences as serious as a total uterine inversion or a complete uterovaginal prolapse. Decision of myomectomy SOS hysterectomy may be considered intra operatively based on 1. Age, 2. Parity, 3. Severity of symptoms and 4. Experience of surgeon